Carbon accumulation by Pinus sylvestris forest plantations after different periods of afforestation in a semiarid sandy ecosystem. (12th March 2021) - Huang, Ze; Cui, Zeng; Liu, Yu; Wu, Gao‐Lin
Abstract: The carbon pool is changing in afforestation ecosystems, which vary in their duration since establishment, in many semiarid sand regions. Understanding this is important for the management of the planted forest. The present study explored the dynamics of afforested forest carbon pool in a semiarid sandy ecosystem, northwest China. We studied afforested forests of pine ( Pinus sylvestris ) of five afforestation ages (20, 30, 40, 50, and 60 years since planting, and bare sand as control), the carbon storage and carbon sequestration rate of the forest aboveground biomass layer, surface litter layer, and soil layer (0–50 cm) were calculated, and the soil water content and soil organic carbon of 0–400 cm soil depth were measured. The results showed that the carbon sequestration rate was highest after 20–30 years, with 0.58 Mg C ha −1 yr −1 in the soil layer (0–50 cm). We found a rate of 0.13 Mg C ha −1 yr −1 in the surface litter layer, and a rate of 20.79 Mg C ha −1 yr −1 in the forest aboveground biomass layer. The carbon storage of the forest aboveground biomass layer was highest after 30–40 years, and the carbon storage of the surface litter increased with time. In the soil layer, the carbon storage at 0–10 cm depth was highest after 60 years, the carbon storage at 20–50 cm depth increased soon after afforestation and then decreased afterward with increasing afforestation ages with the maximum for 20‐50 cm occurring after 30–40 years. The total carbon storage [the forest aboveground biomass layer, surface litter layer and soil layer (0‐50 cm)] was higher when afforestation ages reached around 30 years, after that it decreased with increasing afforestation age. Our research improves the understanding of the P. sylvestris forest ecosystem carbon sequestration in a semiarid sandy area.